COMPLICATIONS DEVELOPED IN PATIENTS WITH CONTINUOUS RENAL REPLACEMENT THERAPY IN THE INTENSIVE CARE UNIT AND NURSING INTERVENTIONS - TÜLÜCE, Derya; BAYRAK KAHRAMAN, Burcu; ŞİMŞEK, Tuba (Göbeklitepe Medical Science Journal, 2022)
This study is to determine the complications developing in patients undergoing continuous renal replacement therapy in an intensive care unit and nursing interventions to prevent these complications. Along with the socio-demographic and clinical characteristic of the patients, complication development status and nursing interventions for developing complications were determined. Data were evaluated with mean, standard deviation and frequency. In this descriptive study, a total of 48 CRRTs were applied to 27 patients hospitalized in the general intensive care units of a university hospital between 02 January 2019 and 02 January 2020. The average age of the patients is 62.92+20.13, APACHE II 25.92+5.33, the duration of stay in intensive care is 23.73+23.67 days. Common first three complications in patients undergoing CRRT; 75.0% hypotension, 47.9% vascular access problem, 43.8% system clotting. Nursing interventions related to common complications have been defined as giving the patient an appropriate position, checking the pressure indicators of the hemofiltration device, checking the arterial and venous pressures and ultrafiltration rate on the indicators of the device, hourly fluid inlet and outlet was followed, vital signs were monitored hourly. It was found that many complications developed in patients undergoing CRRT and nurses in the intensive care unit applied basic nursing interventions. There were not sufficient.